Hedendaagse populêre voorligting oor die verhouding tussen die manlike en vroulike geslag: besinning oor ’n evolusionistiese etiek - B. J. van der Walt (In die Skriflig, 2006)
Contemporary popular guidance on the relationship between male and female: reflections on an evolutionistic ethics This investigation is undertaken for the following reasons: The theoretical question about the nature and meaning of human sexuality is firstly important, because sexuality is an essential element of being human. Secondly, it is also a practical problem. How does a “normal” man or woman differ from each other? How can one know that you are behaving properly as man/woman? A third reason for this exploration is the fact that much of the scientific research done on this issue is nowadays popularised in all kinds of articles and books providing practical guidance for conduct as man/woman. Many of these publications are, however, inspired by Darwinism. The problem of sexuality is accordingly tackled in the following steps: As an introduction, a distinction is made between sex, sexuality and gender. Then the message of a popular book about this issue is discussed. This is followed by identifying the worldviewish and philosophical background of such kinds of books. The article is closed by a few preliminary conclusions. (In a follow-up article the socio-biological background of the evolutionistic view on sexuality will be investigated, which will conclude with a Christian philosophical alternative.)